Removal Co(II) Ions in Aqueous Solution using Fe-MCM-41: Penghilangan Ion Co(II) dalam Larutan Berair menggunakan Fe-MCM-41 - Syamsuri, M. Mahfudz Fauzi; Febriani, Weni; Sutarno, Sutarno; Suyanta, Suyanta (Stannum : Jurnal Sains dan Terapan Kimia, 2024)
The removal of Co(II) ions using Fe-MCM-41 adsorbent was studied. Fe-MCM-41 was synthesized by the sonochemical method and then interacted with solutions containing Co(II) ions at various concentrations. The Langmuir equation indicated monolayer adsorption could be well-fitted for the adsorption isotherms. The maximum adsorption capacity of Co(II) ions on Fe-MCM-41 was 62.89 mg/g. Therefore, it could be conclude that the concentration of Co(II) ions in an aqueous solution can be reduced by using Fe-MCM-41 adsorbent.